Reconstruction of The Authority to Fill Vacancies The Position of Regional Head in The Perspective of Constitutional Democracy In Indonesia - Bakhri, Muhammad Said; Sugnda, Atma; Ismail, Ismail (Sahabat Publikasi, 2025)
The appointment of interim regional heads (Pj) by the President or the Minister of Home Affairs to fill regional leadership vacancies has become a dominant practice in Indonesia's constitutional system following the implementation of simultaneous regional elections. Although this practice is regulated by statutory law, it raises constitutional concerns that contradict the principles of democracy and the rule of law as stipulated in Articles 1(3) and 18(4) of the 1945 Constitution of the Republic of Indonesia. This research employs a normative juridical approach using doctrinal, conceptual, historical, and comparative methods to examine the inconsistency between positive legal norms and constitutional principles. The findings indicate that the current model of appointing regional heads is bureaucratic, non-transparent, and non-participatory, creating space for central government dominance without political legitimacy from the people or their regional representatives. This study proposes a reconstructed model of authority that places Regional People's Representative Councils (DPRD) as the primary actors in the appointment process through open nomination, eligibility screening, legislative selection, and formal ratification by the central government. The proposed model aligns more closely with constitutional democracy, enhances political legitimacy, and strengthens accountability in regional governance.